Small- and medium-sized enterprises in cross-border networks: Empirical evidence from the Pearl River Delta - Klaus-Dieter Schmidt (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1997)
The Pearl River Delta is one of the most successful cases of economic re-integration after a long period of separation. Hong Kong's traditional policy of non-interventionism and China's open-door policy have induced a rapid increase in cross-border trade, outward processing and outward investment. The paper focuses on the different modes of integration as well as on the driving forces behind. It argues that small- and medium- sized enterprises have played the pivotal role in the Delta's economic development. Their cross-border operations have been mainly facilitated through two channels: through subcontracting networks among manufacturers and through links with trading houses which are frequently small in size. The paper underlines three main keys to the Delta's economic success: a non-interventionist policy favourable for growth, a pronounced outward orientation in business which consequently exploits complementaries in comparative advantages and, last but not least, the so-called Chinese factor - the special attitudes adopted by local entrepreneurs, their adaptability and flexibility, their work ethics and their common cultural heritage. In some respects, the Pearl River Delta can serve as a model for developing border regions in Central Europe along the former Iron Curtain. Despite their great potential, these regions are integrating only slowly. The paper suggests that border regions after a long period of political and economic division are predestined to become an economic power-house.
Keywords: F2; O53; R12; 330; Grenzgebiet; Regionale Entwicklung; Internationale Wirtschaftsbeziehungen; Klein- und Mittelunternehmen; Unternehmensnetzwerk; Perlflussdelta